NOTCH1 inhibition enhances immunogenicity and sensitizes triple-negative breast cancer to immune checkpoint inhibitors - Ying Gao; Lin Zuo; Yu Zheng; Keyan Sun; Yunhui Gao; Xiaobo Xu; Zengqiang Li; Daiying Zuo (Breast Cancer Research)
Abstract Although immune checkpoint inhibitors (ICIs) have elicited desirable clinical outcomes, their effective application remains an obstacle due to immunologically “cold” tumors that manifest lymphocyte exhaustion or poor infiltration. Hence, exploring new therapeutic strategies to enhance antitumor immunity is important. NOTCH1 has emerged as an oncogene in multiple malignancies and is involved in regulating the tumor microenvironment (TME). Here, we demonstrated that NOTCH1 inhibition enhanced the expression of MHC class I (MHC-I) molecules and antigen presentation-related genes and increased the characteristics of immunogenic cell death (ICD), including calreticulin (CALR) translocation, ATP release, and endoplasmic reticulum (ER) stress signaling activation. These events enhance tumor antigen presentation and immunogenicity in triple-negative breast cancer (TNBC) cells. Furthermore, cellular senescence was observed after NOTCH1 inhibition. We also observed the senescence-associated secretory phenotype (SASP), including the generation of type I and type III interferons, which increased antigen presentation efficacy. Given that Ataxia-telangiectasia mutated kinase (ATM) is closely related to cellular senescence, we confirmed that the enhancement of immunogenicity mediated by NOTCH1 inhibition was dependent on the activation of ATM. More importantly, inhibition of NOTCH1 signaling sensitizes tumors to ICIs therapy in murine TNBC models and promotes antitumor immunity by upregulating lymphocyte infiltration. Collectively, our findings indicate that NOTCH1 inhibition enhances tumor immunogenicity and provides a rationale for developing new combination regimens comprising NOTCH1 inhibitors and ICIs for TNBC treatment.